Argument for the need of investigation of the relationship between body fatness and experimental pain sensitivity - Rehab A. Astita; Osama A. Tashani; Duncan Sharp; Mark I. Johnson (Libyan Journal of Medicine, 2015)
In this communication, we argue about the need for an extensive investigation of the relationship between body fatness and fat distribution and experimental pain to explore the factors that might contribute to the increased prevalence of pain conditions in obese individuals.